Reducing sample consumption for serial crystallography using acoustic drop ejection. (16th August 2019) - Davy, Bradley; Axford, Danny; Beale, John H.; Butryn, Agata; Docker, Peter; Ebrahim, Ali; Leen, Gabriel; Orville, Allen M.; Owen, Robin L.; Aller, Pierre
Abstract : A new approach for efficiently loading fixed targets for serial crystallography using acoustic dispensing is presented. Abstract : Efficient sample delivery is an essential aspect of serial crystallography at both synchrotrons and X‐ray free‐electron lasers. Rastering fixed target chips through the X‐ray beam is an efficient method for serial delivery from the perspectives of both sample consumption and beam time usage. Here, an approach for loading fixed targets using acoustic drop ejection is presented that does not compromise crystal quality, can reduce sample consumption by more than an order of magnitude and allows serial diffraction to be collected from a larger proportion of the crystals in the slurry.